Collation of resources within a regional antimicrobial pharmacy group. Issue 2 (28th February 2020) - Bond, Stuart; Lee-Milner, Jade
Abstract : Background: Previous regional antimicrobial meetings identified duplication of antimicrobial stewardship work in Acute trusts. In 2018, collation of guidelines for hospital acquired pneumonia, community acquired pneumonia and urinary tract infections led to creation of exemplar guidelines. All documents were emailed, which was inefficient due to volume, with no central repository that could be accessed across sites. Given the regional shortage of microbiologists, easy access to job descriptions and business cases was considered essential to improvement of pharmacy staff resources regionally. Aim: To create an open access regional hub for antimicrobial resources within Yorkshire and the Humber using the Specialist Pharmacy Service (SPS) website. Methods: The Yorkshire and Humber Antimicrobial Pharmacy Group's objective is to continuously improve antimicrobial stewardship and infection management through networking, sharing best practice, learning, peer support and joint working/initiatives. Starting in March 2019, resources were submitted to the SPS website. Results: A total of nine job descriptions were uploaded, along with members of the group, educational links such as the #todipornottodip campaign, terms of reference, annual workplan, meeting agendas and a brief summary of the group's objectives and regional geography. Conclusion: The SPS website has facilitated a more efficient sharing of regional antimicrobial stewardship resources. Further work is warranted for sharing education resources, and business cases that don't contain commercial information. As the site is open access, a decision was made to continue emailing meeting minutes.